2022
DOI: 10.33546/bnj.2127
|View full text |Cite
|
Sign up to set email alerts
|

Developing, validating, and pre-testing of a diabetic care self-management mobile health application: A technology-based intervention for patients with diabetes in Malaysia

Abstract: Background: Technology-based intervention showed a promising approach to health promotion strategies. There had been limited knowledge of the existing program for technology-based intervention in promoting foot care and dietary behavior modification. Thus, a mobile app was developed as an alternative strategy for promoting foot care and dietary behavior modification. Objective: This paper aims to elaborate on the process of developing, validating, and examining the Diabetic Care Self-Management Mobile Health A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The characteristics of the included studies are summarized in Table 1 . Of the 157 included publications, 132 (84.1%) either described usability testing or were original research papers [ 32 - 49 , 51 , 52 , 55 , 56 , 58 - 65 , 67 - 75 , 77 - 81 , 83 , 85 - 87 , 89 - 107 , 110 , 112 - 117 , 119 - 124 , 126 , 129 , 130 , 132 - 134 , 136 , 138 , 140 - 145 , 147 - 160 , 162 - 169 , 171 - 173 , 175 - 187 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of the included studies are summarized in Table 1 . Of the 157 included publications, 132 (84.1%) either described usability testing or were original research papers [ 32 - 49 , 51 , 52 , 55 , 56 , 58 - 65 , 67 - 75 , 77 - 81 , 83 , 85 - 87 , 89 - 107 , 110 , 112 - 117 , 119 - 124 , 126 , 129 , 130 , 132 - 134 , 136 , 138 , 140 - 145 , 147 - 160 , 162 - 169 , 171 - 173 , 175 - 187 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors indicated that nurses took on between 1 and 4 roles within a development phase and more frequently took on a greater number of roles during earlier development phases. In total, 36% (12/33) of the publications describing the planning phase indicated nurses taking on >1 role [ 85 , 92 , 102 , 104 , 110 , 123 , 125 , 126 , 134 , 136 , 139 , 152 ]. Nurses taking on >1 role grew to 42 (43%) out of 98 publications in the requirements gathering phase [ 36 , 37 , 39 , 52 , 55 , 56 , 58 , 61 , 78 , 83 , 84 , 86 , 89 , 92 , 99 , 101 , 104 , 110 , 114 , 116 , 123 , 125 , 126 , 129 , 132 , 134 , 136 , 139 , 146 , 151 , 153 , 158 , 164 - 169 , 171 , 173 , 184 , 188 ] and 50 (44.6%) out of 112 publications in the design and prototyping phase [ 34 , 36 , 37 , 39 , 42 , 43 , 45 , 46 , 51 , 56 - 58 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Diabetic Care Self-Management Mobile Health Application (Diabetic Care App) was developed by the researcher. The app was validated by a team of experts with a good content validity score (1.00) during the validity assessment by the researcher (Firdaus et al, 2022 ). The Diabetes Care App, developed for Android user phones, has six main menus: Foot Care Activity, Foot Care Exercise, Foot Care Records, Foot Care Tips, Diabetic Food Plate, and Food Calorie Tips.…”
Section: Methodsmentioning
confidence: 99%